The Influence of Traditional Sports Invitation on Interest in Learning Physical Education Junior High School Students in Jayapura City (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this study was to determine the effect of traditional sports on the interest in learning Physical Education and Recreation in junior high school students in Jayapura City. This type of research is quantitative. Quantitative Research is research where research data is in the form of numbers..The approach used is One Group Pretest Posttest Design. based on the results of the hypothesis test, there is a significant influence between traditional sports invitations on the interest in learning Physical Education, Health and Recreation of junior high school students. Test the hypothesis using the help of SPSS version 22 , namely using the t test. By making a decision, if the significance value (2 tailed ) <0.05, there is a significant influence between traditional sports invitations on the interest in learning Physical Education, Health and Recreation of junior high school students in the city of Jayapura. From the results of the analysis using the paired sample test, the value of Sig.(2-tailed) is 0.000 <0.005, so there is a significant effect. the conclusion is that the effect of traditional sports invitations on the interest in learning Physical Education junior high school students in Jayapura City is in the high category . Extrinsic factors have a significant impact on physical education learning. By making variations in learning through traditional sports, it can increase student interest in learning.